Five years melioidosis registry data from 2011 to 2015 in Pahang, Malaysia: a retrospective study - How, Soon Hin; Zainulabid, Ummu Afeera; Mohd Ibrahim, Mohamad Shafiq; Mahmud, Fatihah; Lim, Bee Chiu; Bhajan Singh, Kiren Kaur; Loh, Tian Chee; Ken, Voon Fong; Sulong, Mohd Rahim (Bangladesh Infection Research Association, 2023)
Background: Melioidosis cases were conducted throughout the state of Pahang, Malaysia, from 2000 to 2004, and found that there were high annual incidences and mortality rates among melioidosis patients. A series of programs on medical education has since been introduced throughout Pahang, and a registry has been created to track the effects.